Mean and full field homogenization of artificial long fiber reinforced thermoset polymers. Issue 1 (15th March 2018) - Kehrer, Loredana; Pinter, Pascal; Böhlke, Thomas
Abstract: Based on two artificial microstructures representing a long fiber reinforced thermoset material, the effective linear elastic material properties are calculated by both a mean and a full field homogenization method. Concerning the mean field method, the effective elastic material properties are approximated using the homogenization scheme by Mori and Tanaka, formulated explicitly in terms of orientation averages. This allows to use orienation tensors of 2nd and 4th order describing the orientation information on the micro level. The full field method is based on the fast Fourier transformation (FFT), for which the effective material properties are determined by volume averaging. The comparison between both methods show good agreements, the deviations are in the range between 2% and 12%. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)